2012
DOI: 10.1242/jeb.069492
|View full text |Cite
|
Sign up to set email alerts
|

Smelling, feeling, tasting and touching: behavioral and neural integration of antennular chemosensory and mechanosensory inputs in the crayfish

Abstract: SummaryCrustaceans possess two pairs of prominent, movable sense organs on the rostral aspect of their bodies termed antennae: (1) a relatively short, usually bifurcate pair, the 1st antennae, also referred to as antennules, and (2) a much longer, uniramous pair, the 2nd antennae, or just ʻantennaeʼ. The antennules are equipped with diverse arrays of six or more types of cuticular setae, most of which are believed to have a sensory function. Axons from these structures course within the antennular nerve to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 59 publications
0
39
0
Order By: Relevance
“…1E, F), an arrangement that corresponds to the malacostracan organization of long haptic sensilla (guard sensilla) with mechanosensory functions (Mellon, 2012) flanking rows of chemosensory aesthetascs (Hallberg and Skog, 2011), as along the caudal edge of Nebalia antennules (Martin et al, 1996). In Waptia, pairs of long slender sensilla extend laterally and forward from the ventral side of the antennule (Fig.…”
Section: Sensory Organization Of Waptia: Antennules (Figs 1 and 6)mentioning
confidence: 98%
See 1 more Smart Citation
“…1E, F), an arrangement that corresponds to the malacostracan organization of long haptic sensilla (guard sensilla) with mechanosensory functions (Mellon, 2012) flanking rows of chemosensory aesthetascs (Hallberg and Skog, 2011), as along the caudal edge of Nebalia antennules (Martin et al, 1996). In Waptia, pairs of long slender sensilla extend laterally and forward from the ventral side of the antennule (Fig.…”
Section: Sensory Organization Of Waptia: Antennules (Figs 1 and 6)mentioning
confidence: 98%
“…Whether certain setae housed both contact chemosensory and mechanosensory receptors, as occurs in modern crustaceans, is unknown. There are no external markers that would differentiate these from exclusively tactile sensilla, but there is every reason to suppose that Waptia's antennae served multisensory functions comparable to those described for modern decapods (Mellon, 2012).…”
Section: Sensory Organization Of Waptia: Antennules (Figs 1 and 6)mentioning
confidence: 99%
“…Odorants in the benthic flow are carried to the olfactory organs of the animal through turbulent water currents and diffuse toward the surface of the organs where chemoreceptors are located. These olfactory organs also contain mechano-receptors that provide information about the turbulent flow, and together with odorant concentration help the animal locate the source of the chemical plume [7]. Animals use a variety of sensing strategies to orient themselves in the direction of the plume source depending on the flow regimes they operate in [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, concentration and flow cues simultaneously excite chemoreceptors and mechanoreceptors of the antennules during flicking. In addition, many invertebrate organisms, including the spiny lobster P. argus [36], and crayfish P. clarkii [7], contain bimodal chemo-mechanoreceptors on their antennules that respond to both odorants and flow. For P. clarkii , local deutocerebral interneurons integrate hydrodynamic and odorant inputs, and the response of these central elements is enhanced when both flow and odorant stimulation occurs together [31].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that, along the antennule of the freshwater crayfish, there were four predominant mechanosensory sensilla, which were crucial for detecting their predators, mates and varying environmental substrates [88]. In this regard, a numerical model was proposed to confirm the relationship between the four sensilla morphologies and the sensitivity in sensing the flow perturbations within the crayfish's surrounding fluid [56] …”
Section: Physical Conversion Filtering and Amplification Of Stimulimentioning
confidence: 99%